Wisdom of the Body in Sport and Exercise Practices - Pisk Jernej (Sciendo, 2017)
Two alternative ancient views on medicine and health can be distinguished in western antiquity: first, that the knowledge of the doctor is sufficient, and second, that health is primarily a consequence of adapting one's own life to the wisdom of the body. The body works according to its own laws, has its own "logic," and speaks its own language. Therefore, listening to the body can be an important source of information for a healthy human life. The body is not merely an object for human manipulation and "the prison of the soul," but a source of learning and knowledge. It seems that people rarely listen to their own bodies; however, the ancient wisdom of listening to the body is still present and cultivated in modern sports training. Good athletes and trainers are the ones who learn from the body and recognize its messages. In this article, we focus on four aspects of wisdom of the body, presented through four virtues: prudence, justice, fortitude, and temperance. The body teaches us temperance and justice; for example, when someone exaggerates too much, the body produces the feeling of pain. The body is a source of fortitude and persistence when rest and healing is needed. The body is a source of prudence or truth about oneself when we face the physical demands of sport. Therefore, through modern sports practices, the perennial wisdom of the body is still accessible to the modern man.